High intensity crossfit training compared to high intensity swimming: A pre-post trial to assess the impact on body composition, muscle strength and resting energy expenditure - Perna, S.; Bologna, C.; Degli Agosti, I.; Rondanelli, M. (Asian Journal of Sports Medicine, 2018)
Objectives: The aim of this study was to evaluate the impact of two different forms of high intensity training i.e. power CrossFit and intermittent swimming, on body composition markers, max strength and resting energy expenditure.